2021
DOI: 10.1371/journal.pone.0258697
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical outcomes of patients with mild symptoms of coronavirus disease 2019 (COVID-19) discharged from the emergency department

Abstract: Introduction This study was performed to determine the clinical outcomes of patients with mild symptoms of COVID-19 discharged from the emergency department. Methods The present descriptive-analytical cross-sectional study was performed on 400 patients discharged with a diagnosis of COVID-19 from the emergency departments of hospitals affiliated to Tabriz University of Medical Sciences in the time period of 21 March-21 June, 2020. The disease characteristics and demographic data were collected by phone calls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…However, in line with previous studies, we see higher mortality rates among men compared to women, particularly for those younger than 68 years [ 10 ]. Also, in line with previous reports, we find that a significant share of those who died, died within the first 10 days ( S1 Fig ) [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, in line with previous studies, we see higher mortality rates among men compared to women, particularly for those younger than 68 years [ 10 ]. Also, in line with previous reports, we find that a significant share of those who died, died within the first 10 days ( S1 Fig ) [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…The impact of comorbidity was significant (p<0.05) on the patient's oxygen saturation (Table 5). Bagi and co-workers (2021) reported that the average percentage of oxygen saturation in COVID-19 patients with moderate symptoms was 94.91 ± 2.09% (Bagi et al, 2021). Maloberti et al (2021) also reported that the patient's average oxygen saturation at admission and discharge was 95±4% and 97±2%, respectively (Maloberti et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Corona spread in December 2019 and has affected the world since then. Therefore, in addition to the common manifestations of this disease, identifying its rare manifestations can also help to understand this pandemic as much as possible (6)(7)(8)(9). Funding/Support: No funding/support was received for this manuscript.…”
Section: Discussionmentioning
confidence: 99%